α,α-Difluoro-α-phenylsulfanylmethyl carbanion equivalent: a novel gem-difluoromethylenation of carbonyl compounds - Manat Pohmakotr (2018)
α,α-Difluoro-α-phenylsulfanyl-α-trimethylsilylmethane (PhSCF2SiMe3) has been demonstrated as an α,α-difluoro-α-phenylsulfanylmethyl carbanion equivalent. gem-Difluorophenylsulfanylmethylation of carbonyl compounds has been successfully achieved by using PhSCF2SiMe3in the presence of TBAF in THF. The adducts have been converted to the corresponding gem-difluoroalkenes by a novel pyrolytic and/or FVP elimination of the β-hydroxy-α-phenylsufinyl derivatives under reduced pressure. © 2006 Elsevier Ltd. All rights reserved.